2020
DOI: 10.5507/tots.2019.011
|View full text |Cite
|
Sign up to set email alerts
|

Public opinion on connected and automated vehicles: the Czech context

Abstract: Despite limited experience with Connected and automated vehicles (CAVs), the general public has been developing beliefs and attitudes about them. These expected benefits, concerns, trust, and other psychological factors play an important role in the way of accepting and adopting this new technology and as such should be available to various stakeholders. This study surveys the Czech public perceptions and attitudes relevant to policy-making in the area of CAVs. Between November 2017 and January 2018, a represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…A recent survey conducted in eight European countries showed that the elderly are concerned mostly about the safety of automated driverless vehicles and would prefer to travel in autonomous vehicles with the presence of a human supervisor (Kyriakidis et al, 2020 ). Similar findings showing that older and disabled persons are more concerned about reliability and safety of the autonomous vehicles, than younger and non-disabled persons, have been found in several earlier studies (Nielsen and Haustein, 2018 ; Gabrhel et al, 2019 ; Huff et al, 2019 ; Liu et al, 2019 ; Robertson et al, 2019 ; Liang et al, 2020 ). The cost of automatization also seems to concern older people.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…A recent survey conducted in eight European countries showed that the elderly are concerned mostly about the safety of automated driverless vehicles and would prefer to travel in autonomous vehicles with the presence of a human supervisor (Kyriakidis et al, 2020 ). Similar findings showing that older and disabled persons are more concerned about reliability and safety of the autonomous vehicles, than younger and non-disabled persons, have been found in several earlier studies (Nielsen and Haustein, 2018 ; Gabrhel et al, 2019 ; Huff et al, 2019 ; Liu et al, 2019 ; Robertson et al, 2019 ; Liang et al, 2020 ). The cost of automatization also seems to concern older people.…”
Section: Introductionsupporting
confidence: 83%
“…A comparison sample of young or middle-aged drivers would have provided an informative control, and thus a larger study that includes all age groups should be conducted. Earlier studies show that automated vehicles are preferred by typically male, young, highly educated, and those who live in large urban areas (Nielsen and Haustein, 2018 ; Gabrhel et al, 2019 ; Huff et al, 2019 ; Wang and Zhao, 2019 ). The resistance to automated vehicles may be partly explained by the lower risk preference among the elderly: older drivers expect a much higher safety level from the new technology than younger drivers do before accepting it (Liu et al, 2019 ; Wang and Zhao, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Czech respondents were concerned a lot about the inability of AV to adequately respond to unexpected situations and about the failures of AV systems and its effect on road safety. They did not show much concern about the legal aspects of AV use or the private nature of the data, as is the case especially with respondents in the US (Gabrhel, Ježek, & Havlíčková, 2019).…”
Section: Introductionmentioning
confidence: 91%
“…There are also data available from the Czech population. Cultural differences have been demonstrated and, with it, the importance of examining concerns for various demographic characteristics (Gabrhel, Ježek, & Havlíčková, 2019). Czech respondents were concerned a lot about the inability of AV to adequately respond to unexpected situations and about the failures of AV systems and its effect on road safety.…”
Section: Introductionmentioning
confidence: 99%